11C-labeling and preliminary evaluation of pimavanserin as a 5-HT2A receptor PET-radioligand. Issue 5 (1st March 2015) - Andersen, Valdemar L.; Hansen, Hanne D.; Herth, Matthias M.; Dyssegaard, Agnete; Knudsen, Gitte M.; Kristensen, Jesper L.
Graphical abstract: Abstract: Pimavanserin is a selective serotonin 2A receptor (5-HT2A R) inverse agonist that has shown promise for treatment of psychotic symptoms in patients with Parkinson's disease. Here, we detail the 11 C-labeling and subsequently evaluate pimavanserin as a PET-radioligand in pigs. [ 11 C]Pimavanserin was obtained by N-methylation of an appropriate precursor using [ 11 C]MeOTf in acetone at 60 °C giving radiochemical yields in the range of 1–1.7 GBq ( n  = 4). In Danish Landrace pigs the radio ligand readily entered the brain and displayed binding in the cortex in accordance with the distribution of 5-HT2A Rs. However, this binding could not be blocked by either ketanserin or pimavanserin itself, indicating high nonspecific binding. The lack of displacement by the 5-HT2 R antagonist and binding in the thalamus suggests that [ 11 C]pimavanserin is not selective for the 5-HT2A R in pigs.